Model Pembelajaran Edutaiment Dalam Meningkatkan Prestasi Belajar Anak Usia Dini - Okda Jumanti; Husnul Bahri (Al-Khair Journal: Management Education, 2022)
Abstract: Learning models in early childhood education have created difficulties for teachers in developing them, resulting in difficulties in improving children's learning achievement. This paper aims to map and analyze the edutainment learning model for improving early childhood learning achievement. Using a descriptive qualitative method with a literature review approach. The results show that the edutainment learning model can improve early childhood learning achievement. So it can be concluded that early childhood learning achievement is still not optimal due to the limitations of teachers in developing learning models. The relationship of the edutainment learning model, which is a fun and not boring learning model so that it can foster learning motivation, can ultimately improve early childhood learning achievement. Thus it can be suggested, that if you want children's learning achievement to increase, then develop a learning model that is fun and not boring edutainment learning model.Keywords: Edutaimen Learning Model, Children's Learning Achievement, Early Childhood Education Abstrak: Model pembelajaran pada pendidikan anak usia dini telah menciptakan kesulitan bagi guru dalam mengembangkannya, sehingga berakibat kepada kesulitan meningkatkan prestasi belajar anak. Tulisan ini bertujuan untuk memetakan dan menganalisis tentang model pembelajaran edutaiment dalam meningkatkan prestasi belajar anak usia dini. Menggunakan metode kualitatif deskriptif dengan pendekatan kajian pustaka. Hasilnya menunjukkan bahwa model pembelajaran edutaimen dapat meningkatkan prestasi belajar anak usia dini. Sehingga dapat disimpulkan bahwa prestasi belajar anak usia dini masih belum optimal dikarenakan keterbatasan guru dalam mengembangkan model pembelajaran. Hubungan model pembelajaran edutaiment yang merupakan model pembelajaran menyenangkan dan tidak membosankan sehingga dapat menumbuhkan motivasi belajar, pada akhirnya dapat meningkatkan prestasi belajar anak usia dini. Dengan demikian dapat disarankan, jika ingin prestasi belajar anak meningkat, maka kembangkanlah model pembelajaran yang menyenangkan dan tidak membosankan seperti model pembelajaran edutaiment.Kata kunci: Model Pembelajaran Edutaimen, Prestasi Belajar Anak, Pendidikan Anak Usia Dini